RETRACTED: Development of the criteria for estimating the trajectory angle when an object is moving - Lampezhev Abas; Bekmeshov Alexander; Zapolskaya Anna; Gorelov Viktor (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001